Peer effects of corporate social responsibility - CAO, Jie (Institutional Knowledge at Singapore Management University, 2019)
We investigate how firms react to their product-market peers' commitment to and adoption of corporate social responsibility (CSR) using a regression discontinuity design approach. Relying on the passage or failure of CSR proposals by a narrow margin of votes during shareholder meetings, we find the passage of a close-call CSR proposal and its implementation are followed by the adoption of similar CSR practices by peer firms. In addition, peers that have greater difficulty in catching up with the voting firm in CSR experience significantly lower stock returns around the passage, consistent with the notion that the spillover effect of the adoption of CSR is a strategic response to competitive threat. Using alternative definitions of peers and examining underlying mechanisms, we further rule out alternative explanations, such as that based on propagation by financial intermediaries.